Patients with hepatic oligometastatic pancreatic body/tail ductal adenocarcinoma may benefit from synchronous resection. Issue 1 (January 2020) - Yang, Jianyu; Zhang, Junfeng; Lui, Wei; Huo, Yanmiao; Fu, Xueliang; Yang, Minwei; Hua, Rong; Wang, Liwei; Sun, Yongwei
Abstract: Background: Synchronous resection of primary pancreatic ductal adenocarcinoma (PDAC) and liver metastases in highly selective patients is being accepted based on oncology research progress showing safe surgical outcomes with low morbidity and mortality. We also tried to determine patients who would benefit from the operation. Methods: From January 2012 to October 2017, 48 patients who underwent synchronous resection of primary PDAC and liver metastases were retrospectively evaluated. Twenty-three of them underwent oligometastatic synchronous resection. Results: The majority of synchronous resection PDAC patients underwent hepatic wedge resection, and no oligometastatic patient was treated with hemihepatectomy. The median overall survival (OS) of the synchronous resection patients was 7.8 months. Hepatic oligometastatic PDAC patients had a longer OS than that of non-oligometastatic synchronous resection patients, systemic chemotherapy patients and palliative patients (16.1 vs 6.4 months, P = 0.02; 16.1 vs 7.6 months, P = 0.02; 16.1 vs 4.3 months, P < 0.0001; respectively). Further analysis showed that localized pancreatic body/tail PDAC had a better OS in oligometastatic patients than in non-oligometastatic synchronous resection patients (16.8 months vs 7.05 months, P = 0.0004) and systemic chemotherapy patients (16.8 months vs 8 months, P = 0.003). Conclusion: Patients with pancreatic body/tail PDAC with liver oligometastases can benefit from synchronous resection.